The cultural influence of Asian cult films: Asian young generation's fascination changed from the mainstream to the margins - Lin, BingXiu (2024)
This study aims to analyze the cultural impact of Asian cult films on the younger generation in Asia and explore the shift in preferences of young people from mainstream films to marginal Asian cult films. Through quantitative research methods, this study will use an online questionnaire to collect primary data. The questionnaire was created through Google Form and distributed to various social media platforms and other countries in Asia to collect data from young people in Asia. The collected data will be analyzed using chart. The purpose of this study is to identify the appeal, attention and engagement of mainstream and Asian cult films on young people, explore why these types of films have this trend, what attracts young people, and whether they recognize this type of film. In addition, it will also be studied whether Asian cult films have an impact on young people's preferences, culture, etc. By conducting a questionnaire survey on young people aged 15 to 30 in Asia, the research results are expected to show the reasons for the shift in the preferences of young people in Asia and the impact of this type of film on young people in Asia.